Criminal minds. The ninth season [videorecording (DVD)] - Davis, Jeff, 1975-
In Season 9 of the mind-blowing series "Criminal Minds", FBI's Behavioral Analysis Unit (BAU) knows no boundaries when it comes to tracking down ruthless and unpredictable killers. Unit chief Aaron Hotchner (Thomas Gibson) and Special Agents David Rossi (Joe Mantegna), Alex Blake (Jeanne Tripplehorn), Dr. Spencer Reid (Matthew Gray Gubler), Derek Morgan (Shemar Moore) and Jennifer "JJ" Jareau (A.J. Cook) use the scientific art of profiling and psychological tactics to solve the FBI's most extreme and violent cases. With the help of skilled hacker and technical analyst, Penelope Garcia (Kirsten Vangsness), the BAU takes down serial killers, uncovers dark secrets, and saves lives - including one of their own.